IMPLEMENTASI PERENCANAAN STRATEGIS DALAM MENINGKATKAN MUTU TENAGA PENDIDIK SD IT INSAN HARAPAN KOTA BATAM - Nanang Hartanto (UNISAN JURNAL, 2024)
Strategic planning is the key to improving the quality of teaching staff in educational institutions. This research aims to examine the implementation of strategic planning in improving the quality of teaching staff at SD IT Insan Harapan, Batam City. The research method used is literature study and field observation. The research results show that the implementation of strategic planning has a positive impact on the quality of learning and student achievement. First, strategic planning allows institutions to identify needs for developing the competency of teaching staff. With careful planning, institutions can design training and development programs that are in accordance with the vision, mission and goals of the institution. Second, the implementation of strategic planning allows institutions to design curriculum development programs that are relevant to the latest developments in the world of education. With a relevant curriculum, teaching staff can provide learning that is in line with the demands of the times and developments in science. Apart from that, strategic planning also allows institutions to carry out regular monitoring and evaluation of the performance of their teaching staff. By carrying out monitoring and evaluation, institutions can find out to what extent teaching staff have achieved the targets that have been set. This will assist the institution in determining the necessary corrective steps. In an effort to improve the quality of its teaching staff, this institution is also active in developing collaborative networks with various educational institutions and other related agencies. By collaborating, institutions can broaden the insight and knowledge of their teaching staff, so they are able to provide better learning to students. By implementing mature and focused strategic planning, SD IT Insan Harapan Batam City has succeeded in improving the quality of its teaching staff. This is reflected in improving the quality of learning and student achievement. Therefore, strategic planning in improving the quality of teaching staff is a very effective and efficient step in improving the quality of education. Keywords: